Effects of Chronic Kidney Disease on Some Liver Enzymes Activity Before and After Dialysis (Journal of the College of Basic Education, 2022)
The aim of the study is to compare the activity level of some liver enzymes such as aspartate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (ALP) of chronic kidney disease (CKD) patient before and after dialysis. 50 blood samples of male and female with chronic kidney disease compared with (55) healthy persons samples as control group ,both group aged between 20-65 years and have no history of liver diseases. The results of study showed a decrease (P<0.001) in activity level of (AST) and (ALT) ,while the study showed elevated (P<0.001) in activity level of (ALP) in serum of CKD patients before and after dialysis in compared with control group for male and female.